Regulatory elements in the first intron contribute to transcriptional regulation of the 3 tubulin gene by 20-hydroxyecdysone in Drosophila Kc cells. - Bruhat, A.; Tourmente, S.; Chapel, S.; Sobrier, M.L.; Couderc, J.L.; Dastugue, B. (Nucleic Acids Research, 1990)
We have studied the transcriptional regulation of the beta 3 tubulin gene by the steroid hormone 20-hydroxyecdysone (20-OH-E) in Drosophila Kc cells. A series of hybrid genes with varying tubulin gene lengths driving the bacterial chloramphenicol acetyl transferase (CAT) gene were constructed. The promoter activity was assayed after transient expression in Kc cells, in the presence or absence of 20-OH-E. We find that 0.91Kb upstream from the transcription start site contain one or several hormone independent positive cis-acting elements, responsible for the constitutive expression of the beta 3 tubulin gene. In the large (4.5 Kb) first intron of this gene, we identified additional hormone dependent negative and positive regulatory elements, which can act in both directions and in a position-independence manner. Then, the negative intron element(s), which repress the transcription in the absence of 20-OH-E has characteristics of silencer.